Accuracy of ICD-10-CM encounter diagnoses from health records for identifying self-harm events. (26th August 2022) - Simon, Gregory E; Shortreed, Susan M; Boggs, Jennifer M; Clarke, Gregory N; Rossom, Rebecca C; Richards, Julie E; Beck, Arne; Ahmedani, Brian K; Coleman, Karen J; Bhakta, Bhumi; Stewart, Christine C; Sterling, Stacy; et al.
Abstract: Objective: Assess the accuracy of ICD-10-CM coding of self-harm injuries and poisonings to identify self-harm events. Materials and Methods: In 7 integrated health systems, records data identified patients reporting frequent suicidal ideation. Records then identified subsequent ICD-10-CM injury and poisoning codes indicating self-harm as well as selected codes in 3 categories where uncoded self-harm events might be found: injuries and poisonings coded as undetermined intent, those coded accidental, and injuries with no coding of intent. For injury and poisoning encounters with diagnoses in those 4 groups, relevant clinical text was extracted from records and assessed by a blinded panel regarding documentation of self-harm intent. Results: Diagnostic codes selected for review include all codes for self-harm, 43 codes for undetermined intent, 26 codes for accidental intent, and 46 codes for injuries without coding of intent. Clinical text was available for review for 285 events originally coded as self-harm, 85 coded as undetermined intent, 302 coded as accidents, and 438 injury events with no coding of intent. Blinded review of full-text clinical records found documentation of self-harm intent in 254 (89.1%) of those originally coded as self-harm, 24 (28.2%) of those coded as undetermined, 24 (7.9%) of those coded as accidental, and 48 (11.0%) of those without coding of intent. Conclusions: Among patients at high risk, nearly 90% of injuries and poisonings with ICD-10-CM coding of self-harm have documentation of self-harm intent. Reliance on ICD-10-CM coding of intent to identify self-harm would fail to include a small proportion of true self-harm events.